1998
DOI: 10.1146/annurev.arplant.49.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Signal Transduction

Abstract: The plant hormone abscisic acid (ABA) plays a major role in seed maturation and germination, as well as in adaptation to abiotic environmental stresses. ABA promotes stomatal closure by rapidly altering ion fluxes in guard cells. Other ABA actions involve modifications of gene expression, and the analysis of ABA-responsive promoters has revealed a diversity of potential cis-acting regulatory elements. The nature of the ABA receptor(s) remains unknown. In contrast, combined biophysical, genetic, and molecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
767
0
13

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,084 publications
(806 citation statements)
references
References 170 publications
16
767
0
13
Order By: Relevance
“…ABA signalling is known to be important in gene responses under osmotic stress [4]. We investigated the possible involvement of ABA in Sus gene expression by two different approaches : (1) by feeding ABA to detached leaves and (2) by using ABAdeficient Arabidopsis mutants in a cold stress experiment.…”
Section: Role Of Aba In Sus Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA signalling is known to be important in gene responses under osmotic stress [4]. We investigated the possible involvement of ABA in Sus gene expression by two different approaches : (1) by feeding ABA to detached leaves and (2) by using ABAdeficient Arabidopsis mutants in a cold stress experiment.…”
Section: Role Of Aba In Sus Expressionmentioning
confidence: 99%
“…Drought, high salt concentration and cold stresses are all characterized by dehydration and can be classified as water\osmotic stress. It is not yet fully understood how plants can sense osmotic stress, but it is clear that abscisic acid (ABA) is involved in the expression of a number of stress-responsive genes [4]. However, studies conducted on ABA-deficient or ABA-insensitive mutants have indicated that some of these genes are expressed independently of ABA [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the seed, ABA is thought to regulate several processes during late embryogenesis including the induction of seed dormancy, the accumulation of nutritive reserves and the acquisition of desiccation tolerance. These events are associated with the expression of specific sets of mRNA (Leung and Giraudat, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and/or H 2 O 2 act as second messengers of ABA-induced stomatal closure and gene expression under abiotic stresses (30,31). Transient expression analysis revealed that IP 3 and cyclic ADP ribose (cADPR)-gated calcium channels are involved in ABA-induced cytosolic Ca 2+ oscillations (32).…”
Section: Second Messengersmentioning
confidence: 99%